Rents in the political economy of colonial Angola – from the coffee boom to Cabinda Gulf - Santos, Maciel (The Journal of US Africa -Studies, 2023)
Angolan agricultural and mining capital benefited from a long-lasting boom until the mid 1950s but afterwards the world market of tropical commodities changed and agricultural capitals entered into a trend of falling profit rates. This paper tries to evaluate this fall and to describe how it was countered by public policies. In fact, during the last two decades before 1974 the colonial State implemented expenditure amounting to more than a 1 billion USD. The State expenditure was funded by the taxation of mineral rents, mainly coming from the diamond and oil sectors. The local reinvestment of mineral rents, as the recent evolution of the petrostates shows, was an exceptional historical experience. In late colonial Angola capital accumulation came to depend on an increasingly smaller number of rent-generating corporations (in fact, two) and so did the State military expenditure, which included a colonial war budget. This situation generated a political flaw: one of those corporations, Cabinda Gulf Oil, was an affiliate of the Gulf Oil Corporation and the visibility of this association led to a public campaign in the US led by a Congregationalist Church. The campaign against the presence of Gulf in Angola was obviously not successful. Still this model of rent-distributing could have hardly last in a capitalist world market and therefore it survived the United Church efforts for only one year more. Keywords: Rent; Profit rate; Angola; Oil; Cabinda Gulf Oil.